대구농수산물도매시장 활성화 방안 - 국승용 (한국농촌경제연구원, 2007)
The purposes of this research are re-establishing the roles and functions of Daegu-si Bukbu agriculture and marin products wholesale market (henceforth Daegu wholesale market), preparing the plans for improving transaction institutes and a supervision and operation system, and providing the maintenance and improvement plan of facilities in order to confront internal and external changes in Daegu wholesale market and marketing environment. Daegu wholesale market opened in 1998 and has the land of 166,716㎡ and the floor space of 95,784㎡. Daegu wholesale market is ranked third in the volume of transaction among 32 nationwide public agricultural products wholesale market and transacts the agricultural products of 385 thou. ton and the marine products of 18 thou. ton. In Daegu wholesale market, five fruit and vegetable corporations and two marine products corporations operate as wholesale market companies. 316 agro-products intermediary wholesalers and 65 marine products intermediary wholesalers operate. The transaction volume of Daegu wholesale market tends to decline over the past five years like many other public wholesale markets. This is due to poor environment for logistics, the growth of superstores and increasing direct purchase by them in producing areas, poor management of wholesale market companies and intermediary wholesalers, etc. The strategies for the development of Daegu wholesale market are as followings: enhancing the efficiency of logistics through the maintenance and improvement of facilities; aggressive marketing based on the improvement of various market participants' management abilities; the expansion of marketing outlets such as small and medium retailers, restaurants, meal service enterprises through the diversification of transaction institutes. In the short-term, the improvement, of transaction institutes, such as the expansion of non-listed-for-auction-commodities and the partial introduction of the market wholesalers system are necessary. The relocation of facilities should be promoted for efficient logistics. The management efficiency of wholesale market companies and intermediary wholesalers should be improved and the reconstruction of them should achieved through the establishment of strict assessment standards. In the medium- and long-term, moving Daegu wholesale market is necessary for overcoming the present problems. The sufficient land and isolated transaction district are essential for introducing the market wholesalers system. However, it is difficult to arrange it in the current limited area. It is estimated that if the modernization of facilities through the movement of Daegu wholesale market occurred, it would transact the vegetables of 313 thou. ton, the fruits of 59 thou. ton, and the fishery of 22 thou. ton. in 2017. The relocated Daegu wholesale market will need the land of about 400,000㎡ and the floor space of about 105,000㎡ and cost ￦199.5 billion. The economic analyses such as B/C analysis, IRR, NPV about the movement of Daegu wholesale market show that the movement is appropriate. Researchers: Seung-Yong Gouk, Byung-Ryul Kim, Myoungki Lee, Kyung-Chool Cho. Research period: 2006. 12. - 2007. 5. E-mail address: gouksy@krei.re.kr